IMAJERI MENTAL DAN KETERAMPILAN MOTORIK ( STUDI META ANALISIS) - Hidayat, Yusup (Jorpres (Jurnal Olahraga Prestasi), 2010)
This written provides a meta analysis review of the studies on the relationship between imagery mental and motor skill. Imagery is widely used by athletes to enhance motor skill, it was indicated as an effective tool in the improvement of motor skill. The subject in this study are athletes from sport and level different (junior, elite, school, and university atheletes). This study was found that there are positive correlation between imagery mental with motor skill. It was found that after sampling error correction (?) was = 034923 and 53,727% sampling errors that caused by sample heterogeneous, and also measurement error correction (?) was 0,45598 and 7,03742% measurement errors. This finding supports that imagery mental can used to enhance motor skill performance Key words: Imagery mental, sport performance, meta analysis